Considerations regarding pedagogical practice of physical education students at gymnasium - Dana Ioana CRISTEA; Aurelian Andrei CRISTEA; Paul F. DRAGOŞ (Editura Universităţii din Oradea, 2017)
European integration perspective determines major changes in the Romanian economy and society. Education has become, in the turn, the field that starts to know major changes imposed by the new European standards. Considering these statements, the present paper aims to identify issues related to how physical education students are perceived by the middle school pupils in professional practice. Our study is based on a questionnaire with 12 items, applied to secondary school pupils (105 students, 43 girls and 62 boys) from a unit of application activity to improve teaching practice.